KUALITAS PELAYANAN PEMBUATAN SURAT PENGANTAR NIKAH DILIHAT DARI ASPEK RESPONSIVENESS (KETANGGAPAN) PADA KANTOR DESA JARO KECAMATAN JARO KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
The quality of public services is a condition in which the service meets or even exceeds what the consumer expects with the actual performance system of the service provider. The success of the public service process is highly dependent on two parties, namely the bureaucracy (servants) and the public (who are served). The purpose of this study was to find out and analyze the quality of service for making a marriage certificate in terms of responsiveness at the Jaro Village Office, Jaro District, Tabalong Regency. Types and Approaches The approach in this study is a descriptive method with a qualitative approach. In the opinion of Muhammad Ali, to solve and answer the problems that are being faced in the current situation, it is carried out by taking the steps of collecting data, clarifying and making conclusions about a situation objectively in a descriptive situation. The type of research used by the author in this research is descriptive with a qualitative approach that emphasizes the phenomena taken from the steps of collecting data through interviews, observation and documentation. The techniques used for data collection are observation, interviews, and documentation. Primary data sources were obtained from observation and interviews while secondary data were obtained from documentation. The data analysis method used is analysis according to Miles and Hubberman (2014). The results of this study indicate that the Quality of Services for Making Marriage Cover Letters Viewed from the Aspect of Responsiveness at the Jaro Village Office, Jaro District, is categorized as Qualified Enough. Keywords: Quality, Service, Marriage Cover Letter